INCOME OF ROBUSTA COFFEE FARMING ON THE WESTERN SLOPE OF MOUNT SLAMET OF BANYUMAS REGENCY BASED ON LAND AREA LEVELS - Dyah Ethika Nuhdijati; Agus Sutanto; Bambang Sumanto; Purwandaru Widyasunu (Faculty of Animal and Agricultural Science, Diponegoro University, 2020)
Robusta coffee farming business is one of the farmer income resources in Banyumas District with the high economic value, especially on the west slope of Slamet Mountain which has an exclusive taste of the coffee. The main aim of this research is to analyze cost and revenue in every level of broadland strata, and also the contribution of robusta coffee farming business towards farmer’s household income. The method used in this research was descriptive with a survey approach. The sample was determined purposively for farmers who had 11 years old robusta coffee plants. Sixty-nine farmer respondents were determined with the snowball sampling method. The result showed that the average revenue in strata 1 with average broadland up to 0,28 ha was Rp 724.952,00. In the other side the average revenue in strata 2 with the average broadland up to 1,572 ha was Rp 3.605.309. The contribution of Robusta coffee farm income to the income of farmers households on the western slopes of Mount Slamet, Banyumas Regency, strata 1 was 9.24 percent and strata 2 was 80.20 percent. This shows that the robusta strata 1 coffee farming activities make a small contribution, because it is less than 50 percent, so it needs agribusiness-oriented coffee farming.